2005
DOI: 10.1093/gerona/60.10.1304
|View full text |Cite
|
Sign up to set email alerts
|

Gait Velocity as a Single Predictor of Adverse Events in Healthy Seniors Aged 75 Years and Older

Abstract: GV measurement in the ambulatory setting may allow the detection of healthy elderly people at risk for adverse events. These data may suggest that simple assessment of GV is enough to predict adverse events in well functioning older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
399
2
34

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 641 publications
(453 citation statements)
references
References 25 publications
18
399
2
34
Order By: Relevance
“…In a cohort study evaluating gait speed in a group of elderly people, Odasso et al 32 differentiated them into three speed levels (high, moderate and low). They found that the group with the lowest gait speed demonstrated higher incidence of falls, among other adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study evaluating gait speed in a group of elderly people, Odasso et al 32 differentiated them into three speed levels (high, moderate and low). They found that the group with the lowest gait speed demonstrated higher incidence of falls, among other adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8)(9)(10)(11) Walking speed is a simple, objective performance-based measure of lower limb neuromuscular function that not only allows detection of subtle impairments and preclinical diseases but also is a sensitive marker of functional capacity in older adults. (10)(11)(12)(13)(14)(15)(16) For instance, Suzuki and colleagues recently demonstrated that walking speed in older adults was positively ORIGINAL ARTICLE J JBMR correlated with physical performance tests such as handgrip strength or stork standing time. (16) Furthermore, these authors also found a significant positive association between walking speed at a usual pace and serum 25(OH)D concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done through the quantification of the same parameters used in assessment scales, like the time to complete the test in TUGT (see [7]), quantification of mobility or gait parameters associated with fall risk (cf. [55], [56], [57], [58] and [59]) or using machine learning techniques, with the ground truth provided by clinically accepted scales (cf. [47], [32], [48], [6] and as suggested in [50]).…”
Section: Recent Studies On Fall Risk Predictionmentioning
confidence: 99%
“…Brach et al (2011) classified the individuals as having a poor/fair mobility (gait speed inferior to 80cm/s), good mobility (gait speed between 80-100cm/s) and very good mobility (gait speed superior to 100cm/s) [57]. Data from [55] indicated that a slow gait velocity alone in well functioning older people was enough to predict risk for further adverse events. Then, the authors support the idea that the gait velocity test could be used in ambulatory clinics, possibly as an alternative tool to more complex mobility tests performed in clinic environments [55].…”
Section: Gait Parametersmentioning
confidence: 99%
See 1 more Smart Citation